DEVELOPMENT OF SHARIA MAQASHID THEORY IN MODERN TIMES (International Conference on Social and Islamic Studies, 2022)
Al-Syatibi is considered to be the father of maqashid classical scholars through his monumental work al-Muwaffaqat fi Usul al-Syariah. On the other hand, modernization was carried out by Rasyid Ridha who consented to modern cases. Thaha ibn 'Assyria with his monumental work is considered the father of modern maqashid scholars. Jasser Auda with his monumental work Maqasid al-Shariah as Philosophy of Islamic Law: A Systems Approach published by IIIT in London in 2007 is a contemporary maqashid figure who has concerns in the field of Islamic law from a very different generation. This article seeks to systematically reveal the thoughts of Modern and Contemporary Maqashid figures in using the considerations of Maqashid al-Sharia in determining the birth of legal decisions.